Applying microbial biogeography in soil forensics. (January 2019) - Habtom, Habteab; Pasternak, Zohar; Matan, Ofra; Azulay, Chen; Gafny, Ron; Jurkevitch, Edouard
Highlights: Soil microbial DNA profiles correlate to geographic location more than to soil type. At 25–1000 m apart, there is strong distance-decay relationship between soil samples. This may enable pinpointing the source location of a sample to within at least 25 m. At 1–260 km apart, difference between samples correlates to annual precipitation. For forensic applicability, more worldwide validations are required. Abstract: The ubiquity, heterogeneity and transferability of soil makes it useful as evidence in criminal investigations, especially using new methods that survey the microbial DNA it contains. However, to be used effectively and reliably, more needs to be learned about the natural distribution patterns of microbial communities in soil. In this study we examine these patterns in detail, at local to regional scales (2 m–260 km), across an environmental gradient in three different soil types. Geographic location was found to be more important than soil type in determining the microbial community composition: communities from the same site but different soil types, although significantly different from each other, were still much more similar to each other than were communities from the same soil type but from different sites. At a local scale (25–1000 m), distance-decay relationships were observed in all soil types: the farther apart two soil communities were located, even in the same soil type, the more they differed. At regional-scale distances (1–260 km), differences between communities did not increase with increased geographic distance between them, and the dominant factor determining the community profile was the physico-chemical environment, most notably annual precipitation (R 2 = 0.69), soil sodium (R 2 = 0.49) and soil ammonium (R 2 = 0.47) levels. We introduce a likelihood-ratio framework for quantitative evaluation of soil microbial DNA profile evidence in casework. In conclusion, these profiles, along with detailed knowledge of natural soil microbial biogeography, provide valuable forensic information on soil sample comparison and allow the determination of approximate source location on large (hundreds of km) spatial scales. Moreover, at small spatial scales it may enable pinpointing the source location of a sample to within at least 25 m, regardless of soil type and environmental conditions.